The folds and faults kinematic association in Zagros - Ghanbarian, Mohammad Ali; Derakhshani, Reza (Nature Research, 2022)
The Zagros orogenic belt, one of the most prominent and famous collisional belts in the central part of the Alpine-Himalayan orogenic chain, is located between the southern margin of the Central Iranian microcontinent and the northern margin of the Arabian plate. The structural architecture and folds and faults relationships of a significant segment of the south-central part of the Zagros’ hinterland are investigated in this study through stereoscopy of aerial photographs, interpretations of satellite images, consideration of the major ground topographic variations, and field research. This research found that there must have been at least two major deformation events: (1) a ductile phase, which is older than the Eocene, and (2) a semi-brittle deformation stage, which is younger than the early Miocene and is represented by thrusting, folding, and strike-slip faulting. The presence of numerous fault-related folds and fold-accommodation faults in this area demonstrates the close kinematic relationship between folding and faulting. Based on the topographic changes, a major hidden tear fault and a basement hidden back thrust, which play important roles in the architecture of the area, have been suggested.